Enhanced high-gain SLC-ZSI at low-duty region - Bussa V.K.; Singh R.K.; Mahanty R. (My University, 2025)
An enhanced high-gain switched inductor capacitor (LC) Z-source inverter (eSLC-ZSI) is proposed in this study. It has a lesser number of elements to achieve high-gain inversion at low-duty region as compared with the conventional non-isolated high-gain ZSIs. It gives continuous input current at reduced high-frequency ripple, which is essential for the sources such as solar photovoltaic cells, fuel cells and batteries to enhance their lifetime. Owing to its operation at low-duty region (i.e. increased modulation index), it gives high-gain inversion at low harmonic distortion. A detailed mathematical modelling of the proposed enhanced SLC-ZSI is carried out using the developed switching logic. In addition, a comparative analysis is given among the reported ZSIs and the proposed ZSI in terms of number of elements, boosting capability, voltage gain, the volume of the passive elements, voltage and current stresses on the elements. The steady-state behaviour of the proposed ZSI is verified through PSIM-based simulation studies and scaled down 250 W laboratory prototype. Using the experimental results, power losses in different elements of the proposed ZSI are calculated at rated power and its efficiency is measured at different loading conditions. © The Institution of Engineering and Technology 2019.